Oxidative Stress in Ruminants: Nutritional Approaches for Mitigation and Improved Performance: A Review - Baker, Ahmed Gh. (American Journal of Botany and Bioengineering, 2025)
Oxygenic pressure is a fundamental element of the ruminants health, proliferation and productivity. In excess they refer to disturbance and imbalance in the production of (ROS) and the antioxidant function as a result of cellular and metabolic dysfunctions. Sources of major ROS in ruminants, specifically due to environmental toxicants, nutritional imbalance, or an acute pathological process, particularly during special conditions like pregnancy or lactation, are being pointed out in the present review. Which leads to the weak ability of immunity and reduction of growth, milk yield and fertility, and brings huge economic losses to animal husbandry. In diseases where mitigating oxidant stress is advantageous, dietary manipulations can have an impact. We know the presence of vitamins (E, C, β-carotene), trace elements (selenium, zinc, copper, manganese) and phenolic compounds such as polyphenols, flavonoids and essential oils can contribute enormously to ROS scavenging and therefore possibilities of redox environment bartel2005regulation; dou et al. These are changing due to some new strategies recent on the market in order to ensure high integrative bioavailability of dietary antioxidants applied and long-term protection from oxidative aggression: probiotics, prebiotics and nano-supplements (capsulated formulas). Conclusion The hormonal regimens with spermatogenic protocols can definitely be combined to improve growth, reproductive performance, and immunity for sustainable livestock production. The information obtained from nowadays investigational Ialso emphasized importance of one’s diet in relation to antioxidant diet regimen driven by oxidative strain and suitable barding methods found in ruminants to minimized oxidative pressure. However, other fundamental issues such as combinations and doses optimization, determination of long-term effects and measurement of contribution to sustainability still need to be researched to improve ruminants resistance and performance under OS.